2018
DOI: 10.1007/s00122-018-3128-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of powdery mildew resistance QTL in strawberry (Fragaria × ananassa)

Abstract: Key Message Powdery mildew resistance in two strawberry mapping populations is controlled by both stable and transient novel QTL of moderate effect. Some low transferability of QTL across wider germplasm was observed. Abstract The obligate biotrophic fungus Podosphaera aphanis is the causative agent of powdery mildew on cultivated strawberry (Fragaria × ananassa). Genotypes from two bi-parental mapping populations ‘Emily’ × ‘Fenella’ and ‘Redgauntlet’ × ‘Hapil’ were phenotyped for powdery mildew disease severi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 39 publications
5
36
0
Order By: Relevance
“…Overexpression of AtELP3 and AtELP4 in diploid strawberry conferred enhanced resistance to P. aphanis, suggesting that ELP genes may confer resistance against PM [24]. Recent advances in our understanding of resistance against P. aphanis have revealed that it is polygenic and quantitatively inherited [25]. Despite these efforts, little research has focused on the molecular resistance mechanisms of the octoploid strawberry.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of AtELP3 and AtELP4 in diploid strawberry conferred enhanced resistance to P. aphanis, suggesting that ELP genes may confer resistance against PM [24]. Recent advances in our understanding of resistance against P. aphanis have revealed that it is polygenic and quantitatively inherited [25]. Despite these efforts, little research has focused on the molecular resistance mechanisms of the octoploid strawberry.…”
Section: Introductionmentioning
confidence: 99%
“…Crosslink was used to generate linkage maps- a program developed specifically for polyploid plant species 30 . The map orders from 5 populations were combined to make the consensus map as detailed in the study of Harrison et al 31 . Fragaria × ananassa chromosome number is denoted by 1-7 and the sub-genome number is represented by A-D as specified in 32 .…”
Section: Methodsmentioning
confidence: 99%
“…QTL mapping of phenotypic traits was performed through Kruskal-Wallis analysis on mean genotype trait values to identify focal single nucleotide polymorphisms (SNPs). The most significant marker was selected for each QTL and then combined into selection through a stepwise linear regression model using a stepwise regression function [54]. Interval mapping and MQM mapping was conducted in MapQTL® [55].…”
Section: Quantitative Trait Loci (Qtl) Analysismentioning
confidence: 99%